2019
DOI: 10.1093/nar/gkz263
|View full text |Cite
|
Sign up to set email alerts
|

LC8/DYNLL1 is a 53BP1 effector and regulates checkpoint activation

Abstract: The tumor suppressor protein 53BP1 plays key roles in response to DNA double-strand breaks (DSBs) by serving as a master scaffold at the damaged chromatin. Current evidence indicates that 53BP1 assembles a cohort of DNA damage response (DDR) factors to distinctly execute its repertoire of DSB responses, including checkpoint activation and non-homologous end joining (NHEJ) repair. Here, we have uncovered LC8 (a.k.a. DYNLL1) as an important 53BP1 effector. We found that LC8 accumulates at laser-induced DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 75 publications
3
31
0
Order By: Relevance
“…The existence of epigenetic memory seems to be crucial in the process of adaptation to new conditions. DYNLL1 gene was repeatedly linked with DNA repair processes, especially as an effector in non-homologous end joining (NHEJ) repair [46]. DNA methylation decrease in DYNLL1 gene in a CpG island found in exposed subjects in our study could be the reason for intensive NHEJ repair processes in this group.…”
Section: Discussionmentioning
confidence: 51%
“…The existence of epigenetic memory seems to be crucial in the process of adaptation to new conditions. DYNLL1 gene was repeatedly linked with DNA repair processes, especially as an effector in non-homologous end joining (NHEJ) repair [46]. DNA methylation decrease in DYNLL1 gene in a CpG island found in exposed subjects in our study could be the reason for intensive NHEJ repair processes in this group.…”
Section: Discussionmentioning
confidence: 51%
“…When DNA damage occurs within 6 hr, a change in the phosphorylation level of H2A.X can be detected. 9,43 Conclusion U2-AuNP shows outstanding inhibition of GBM in vitro and in vivo. Based on our previous research, we found that the U2-AuNP complex exhibits potential value as a multifunctional therapeutic strategy for inhibiting the EGFR-related pathway and preventing DNA damage repair to GBM.…”
Section: Discussionmentioning
confidence: 97%
“…Transfections were carried out using both Polyethylenimine (PEI) (Polysciences, Inc.) and FuGene HD (Promega) according to the manufacturer's instruction. U2OS RNF168 KO cells 56 were generated using CRISPR/Cas9 method. RNF168 gRNA1-GCATAAACTCGCCTTTTCGA and gRNA2-GGAAGTGGGT GAGTAACCA were cloned into pSpCas9(BB)-2A-Puro (a gift from Fen Zhang-Addgene ID: 48139).…”
Section: Methodsmentioning
confidence: 99%